Pengaruh Brithing Ball Terhadap Tingkat Kecemasan Pada Ibu Hamil TM 3 Dalam Menghadapi Persalinan Di TPMB Amalia Temon Desa Brati - Rosmala Kurnia Dewi; Anggita Septyani Permatasari (LPPM AN Nuur, 2022)
Background: Anxiety comes from a reaction to internal tension from the body or from outside and is controlled by the autonomic nervous system. Anxiety-stricken people will usually feel afraid, tense, worried, anxious and nervous. Unresolved anxiety can also trigger increased pain in labor. Management of anxiety can be done with pharmacological and non-pharmacological therapy, nonpharmacological treatment used by carrying out birth balls. Purpose:The purpose of giving the Birthing Ball method is to provide knowledge and skills to TM 3 pregnant women in dealing with and reducing anxiety levels during labor. Method: The method used in this service is a descriptive survey with implementation techniques through anamnesis, documentation, and observation as well as measuring anxiety levels using a questionnaire. Results:. After being given the Brithing Ball implementation, the average score of the anxiety level of TM III pregnant women, which was originally 51 became 49. Conclusion: The method of carrying out the Brithing Ball is proven to help reduce anxiety levels in mothers giving birth at TPMB Amalia Temon